Is GDF5 gene promoter polymorphism +104T/C associated with osteoarthritis in the Eastern of Turkey population? - Tülüce, Y.; Yildirim, ć°. H.; í–zkol, H.; EdiÌ‡z, L.; Delen, V. (Cellular and Molecular Biology, 2017)
Osteoarthritis (OA) is the most common form of arthritis. Genetic factors have been shown to play important roles in the etiology of OA. The gene growth differentiation factor 5 (GDF5) has been implicated in skeletal development and joint morphogenesis in human and mice. A functional single nucleotide polymorphism (SNP) +104T/C in the 5’-UTR of GDF5 (rs143383) was reported to be associated with osteoarthritis susceptibility in Han Chinese and Japanese populations. Our objective was to assess whether this SNP was also associated with OA in the Eastern Turkey population.A total of 172 cases including 95 patients with idiopathic OA and 77 control cases were recruited into the study. DNA samples were extracted from peripheral blood lymphocytes of all cases by using salting out method. The +104T/C polymorphism was genotyped by PCR-RFLP method. In terms of genotype comparison there wasn’t any correlation between patient and control groups. Frequency of C allele was found to be higher in-patient group than control group and statistical analysis showed a poor correlation in allele frequencies of the +104T/C SNP of GDF5 gene between cases and controls (p<0.05). Significant correlation between GDF5 and OA has been reported in Asian population, especially T alleles were found in higher frequencies and related to OA. Our study did not confirm this association and also in term of T allele. Interestingly, we found higher frequency of C allele in patient group than control group and our results are compatible with the study carried out in Greek population.